SMEs with legally restricted banking access: evidence from the US marijuana industry - Markus Merz; Jan Riepe (Journal of Business Economics, 2021)
This paper examines how legally restricted access to banking services affects small and medium-sized enterprises (SMEs) in a highly developed country. Using a mixed-method approach, we examine the unique situation of the US marijuana industry. The industry benefits from the superior institutional environment in terms of legal protection and the labor market of the United States. However, due to conflicting state and federal laws it has no legal access to banking. We find significant value effects around three major events that affected future access to banking. These results indicate that banking access remains desirable for the marijuana industry. A survey taken by marijuana SMEs provides insights into what banking services are considered most valuable. We find that marijuana SMEs have problems to obtain financing and handle their transactions largely in cash, resulting in transaction inefficiency and high security concerns. Thereby, we shed light on the value of banks for SMEs in developed countries. We complement the literature on financial transaction services by highlighting the value for SMEs in developed markets.
Keywords: D22; G21; M13; M21; O16; O43; 650; Access to banking; Financial development; Small and Medium-sized enterprises; Marijuana firms